Implementation Of Pancasila Education In Raise The Soul Of Nationalism In The Millennial Generation In The Era Of Digitalization - Habibah, Siti Maizul; Pratama, I Putu Ananda Widia; Lusi, Nuraini (Jurnal Civicus, 2024)
Pancasila education in tertiary institutions is necessary considering students are the next generations who carry out the mandate to continue the nation's struggle in the future. As the next generation, students carry out the life of the nation in the midway of the existence of various ideologies in the world which can undermine the existence of Pancasila values. In this era of globalization with advances in information technology that can no longer be prevented , students can quickly get any information. Pancasila reflects the characters of the nations seen from the position of Pancasila in Indonesia as a guideline, purpose, and outlook on life. In addition, Pancasila can be a benchmark for good and bad, especially for the millennials generations. The millennials generations cand to want something that is instant. The impact of this is to make individuals not indifferent to others and consider themselves compared to their surroundings so that these individuals rarely socialize and prefer to depend on technology, especially in urban areas. The implementation _ of this research is to find out how the applications of Pancasila education in arousing a spirit of nationalism in the millennials generation in the digitalization era and to find out how the implementation of Pancasila education in arousing soulism in the millennials generation in the digitalization era. The benefits of conducting this research is expected to provide benefits to the community, as well as private parties who carry out related research